1999
DOI: 10.1007/bf02433192
|View full text |Cite
|
Sign up to set email alerts
|

New endogenous dipeptide cycloprolyl-glycine is similar to piracetam by its mnemotropic selectivity

Abstract: The effects of endogenous dipeptide cycloprolyl-glycine on learning and memory in the model of postconvulsive retrograde amnesia of passive avoidance response in rats depended on the administration schedule. The dipeptide prevented retrograde amnesia, when injected prior to learning, had no effect after postlearning administration, and aggravated amnesia, when injected immediately before retrieval. These data suggest that cycloprolyl-glycine is similar to the standard nootropic piracetam by its mnemotropic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The in vivo investigations of cyclo (Pro—Gly) showed that this dipeptide has pharmacological profile resemble that of Piracetam. Like Piracetam, cyclo (Pro—Gly) possess nootropic [22], neuroprotective, antihypoxic [23] and anxiolytic [24] activities. Evaluation of the effect on memory phases in passive avoidance test in rats demonstrated that cyclo (Pro—Gly) similar to Piracetam is active only when administered before learning.…”
Section: Noopept a Dipeptide Nootropic Drugmentioning
confidence: 99%
“…The in vivo investigations of cyclo (Pro—Gly) showed that this dipeptide has pharmacological profile resemble that of Piracetam. Like Piracetam, cyclo (Pro—Gly) possess nootropic [22], neuroprotective, antihypoxic [23] and anxiolytic [24] activities. Evaluation of the effect on memory phases in passive avoidance test in rats demonstrated that cyclo (Pro—Gly) similar to Piracetam is active only when administered before learning.…”
Section: Noopept a Dipeptide Nootropic Drugmentioning
confidence: 99%
“…Since CPG synthesis in 1991 and its discovery as an endogenous compound in rat brain in 1996 (Gudasheva et al, 1996a), in vitro and animal studies have revealed a wide range of CPG psychotropic activities. It was shown that the dipeptide possesses antiamnesic (Gudasheva et al, 1999), anxiolytic (Seredenin et al, 2002), antihypoxic, and neuroprotective effects (Povarnina et al, 2016). Previously it was shown that CPG chronic administration significantly decreased immobility time in inbred BALB/c mice in the forced swim test (FST) (1 and 2 mg/kg, 2 weeks, i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…Cyclo-L-prolylglycine (CPG) was designed as a potential peptide prototype of piracetam, the classic nootropic drug [1] and was subsequently discovered as endogenous compound in the brain of intact rats in micromolar concentration [2]. CPG is similar to piracetam both in structure and main pharmacological effects; it possesses nootropic [3], anxiolytic [4,5], antihypoxic [6], neuroprotective [6,7], analgesic [8], and antidepressant [9,10] activities at central administration at doses 100-1000 times smaller than those for piracetam. Recently, we have demonstrated CPG to be ampakine, i.e., a positive modulator of AMPA receptors [11].…”
Section: Introductionmentioning
confidence: 99%